The importance of being honest - Nicolas Klein (Theoretical Economics, 2016)
This paper analyzes the case of a principal who wants to provide an agent with proper incentives to explore a hypothesis that can be either true or false. The agent can shirk, thus never proving the hypothesis, or he can avail himself of a known technology to produce fake successes. This latter option either makes the provision of incentives for honesty impossible or does not distort its costs at all. In the latter case, the principal will optimally commit to rewarding later successes even though he only cares about the first one. Indeed, after an honest success, the agent is more optimistic about his ability to generate further successes. This, in turn, provides incentives for the agent to be honest before a first success.
Keywords: C79; D82; D83; O32; 330; Dynamic moral hazard; continuous-time principal-agent models; optimal incentive scheme; experimentation; bandit models; Poisson process; Bayesian learning